Load Transfer Mechanism of Hybrid Pylon Joint with Cells and Bearing Plates - Yongjun Li; Yuqing Liu; Feihua Wang; Fei Yang (Advances in Civil Engineering)
To investigate the load transfer mechanism of the steel-concrete hybrid pylon joint with cells and bearing plates, a theoretical model based on the continuous elastic interlayer method was established. Both the slip effect at the steel-concrete interface and the local compression effect of the bearing plate were considered in the proposed theoretical model. A segment model test with a 1 : 3 scale was carried out to obtain the strain distribution of the hybrid joint and the relative slip between steel and concrete components. Finite element analysis was implemented on the tested segment model, and the structural performance of the tested hybrid joint was compared with the FEA results. The test and analysis results show that the stress of steel and concrete components is at a lower level, and the relative slip between steel and concrete components is extremely limited. The bearing plates and shear connectors are the two load-transferring components and could transfer 40% and 60% of the vertical force into the lower concrete pylon, respectively. The vertical force of shear connectors is at a much lower magnitude within 0.6 times the length of the hybrid joint from the bearing plate and will increase gradually within 0.6 to 1.0 times the length of the hybrid joint. The FEA results are in good agreement with the model test results, and the maximum shear force difference between the theoretical analysis results and the FEA results is less than 10%, proving that the proposed theoretical model can reasonably predict the shear force distribution at the steel-concrete interface of the hybrid joint. In addition, the stiffness of shear connectors has limited effect on the shear force distribution at the steel-concrete interface.